A role for caveola‐forming proteins caveolin‐1 and CAVIN1 in the pro‐invasive response of glioblastoma to osmotic and hydrostatic pressure. Issue 6 (17th February 2020) - Pu, Wenjun; Qiu, Jiawen; Nassar, Zeyad D.; Shaw, Paul N.; McMahon, Kerrie‐Ann; Ferguson, Charles; Parton, Robert G; Riggins, Gregory J.; Harris, Jonathan M.; Parat, Marie‐Odile
Abstract: In solid tumours, elevated interstitial fluid pressure (osmotic and hydrostatic pressure) is a barrier to drug delivery and correlates with poor prognosis. Glioblastoma (GBM) further experience compressive force when growing within a space limited by the skull. Caveolae are proposed to play mechanosensing roles, and caveola‐forming proteins are overexpressed in GBM. We asked whether caveolae mediate the GBM response to osmotic pressure. We evaluated in vitro the influence of spontaneous or experimental down‐regulation of caveola‐forming proteins (caveolin‐1, CAVIN1) on the proteolytic profile and invasiveness of GBM cells in response to osmotic pressure. In response to osmotic pressure, GBM cell lines expressing caveola‐forming proteins up‐regulated plasminogen activator (uPA) and/or matrix metalloproteinases (MMPs), some EMT markers and increased their in vitro invasion potential. Down‐regulation of caveola‐forming proteins impaired this response and prevented hyperosmolarity‐induced mRNA expression of the water channel aquaporin 1. CRISPR ablation of caveola‐forming proteins further lowered expression of matrix proteases and EMT markers in response to hydrostatic pressure, as a model of mechanical force. GBM respond to pressure by increasing matrix‐degrading enzyme production, mesenchymal phenotype and invasion. Caveola‐forming proteins mediate, at least in part, the pro‐invasive response of GBM to pressure. This may represent a novel target in GBM treatment.